NILAI-NILAI TAFSIR TARBAWI DALAM PEMBELAJARAN BERBASIS PENGALAMAN (EXPERIENTIAL LEARNING) - Fitriana, Ida; Mirza, Iskandar (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study is motivated by the gap between the holistic objectives of Islamic Religious Education (IRE), namely spiritual and moral transformation (tazkiyah), and learning practices that are often verbalistic and rote-oriented. To bridge this gap, this study proposes the integration of the Tafsir Tarbawi approach, which extracts educational principles from the Qur'an, with the theory of Experiential Learning from modern pedagogy. Using qualitative research methods of library research and content analysis, this study aims to: (1) analyze the meaning of experience as a source of learning in the epistemology of Tafsir Tarbawi, (2) examine Islamic values in the framework of Experiential Learning, and (3) formulate pedagogical implications for PAI. The results show that Tafsir Tarbawi interprets experience (tajribah) as a divine epistemological path which, through reflection (tadabbur), leads to the strengthening of faith and morals. Core Islamic values such as Tawhid, Akhlak, Ukhuwah, and Rahmah can be effectively internalized through the experiential learning cycle. As a synthesis, this study formulates the TT-EL (Tafsir Tarbawi-Experiential Learning) Model, which offers an operational framework for transforming PAI learning to be more contextual, reflective, and meaningful.